HUBUNGAN SIKAP DENGAN KEPATUHAN PERAWAT DALAM MENCUCI TANGAN DI RUANG RAWAT INAP RUMAH SAKIT SWASTA - Doloksaribu, Eunike Kristien; Lintin, Nathalia; Dewi, Revina Marthalita Sukma; Pakpahan, Martina; Purimahua, Dora Irene (Universitas Tarumanagara, 2021)
Health Care-Associated Infection (HAI) or Nosocomial infection is still a major problem that occurs in hospitals. This results in prolonged treatment, increased resistance to antimicrobials, increased morbidity and mortality, high maintenance costs and decreased quality of care. Nurses interact the most with patients, so nurse compliance in washing hands can affect the spread of nosocomial infections. This study aims to determine the correlation between nurses’ attitudes and compliance with hand washing in an inpatient room at a private hospital in Jakarta. The study is quantitative correlational used cross-sectional design. The total samples was 49 respondents obtained using purposive sampling technique. This study used a questionnaire instrument and observation sheet. Validity and reliability tests for the questionnaire obtained Cronbach Alpha 0.909. Observations among researchers obtained the kappa test results of 0.615.The analysis used univariate and bivariate analyzes. The ethical approval was obtained from the Ethics Committee of the Faculty of Nursing, Universitas Pelita Harapan. In the univariate analysis, it was showed that 27 (55.1%) of nurses had a good attitude in hands washing and 39 (79.6%) of nurses did not comply with hands washing. In the bivariate analysis using the Chi-Square test, it showed that there was no correlation between attitudes and nurse compliance in hand washing in an inpatient room at a private hospital in Jakarta (p value 0.716, 95% CI). Future studies can examine other factors that influence nurse compliance in hand washing compliance such as knowledge, motivation, availability of hand washing facilities, workload, monitoring and role models. Keywords: Hand washing; Compliance; Nurse; Inpatient; Attitude AbstrakInfeksi terkait pelayanan kesehatan atau infeksi nosokomial masih menjadi masalah utama yang terjadi di rumah sakit. Hal ini menyebabkan perawatan yang berkepanjangan, peningkatan resistensi terhadap antimikroba, peningkatan morbiditas dan mortalitas, biaya perawatan tinggi dan menurunnya mutu pelayanan. Perawat paling banyak berinteraksi dengan pasien maka kepatuhan perawat dalam mencuci tangan dapat memengaruhi penyebaran infeksi nosokomial. Penelitian bertujuan untuk mengetahui hubungan sikap dengan kepatuhan perawat mencuci tangan di Ruang Rawat Inap di Satu Rumah Sakit Swasta di Jakarta. Penelitian merupakan kuantitatif korelasional dengan desain cross-sectional. Jumlah sampel yaitu 49 responden yang diperoleh menggunakan purposive sampling. Instrumen berupa kuesioner dan lembar observasi. Uji validitas dan reliabilitas kuesioner didapatkan Cronbach Alpha 0,909. Observasi diantara peneliti didapatkan hasil uji kappa 0,615. Analisis menggunakan analisis univariat dan bivariat. Persetujuan etik didapatkan dari Komite Etik Fakultas Keperawatan Universitas Pelita Harapan. Pada analisis univariat diketahui sebesar 27 (55,1%) perawat memiliki sikap baik dalam mencuci tangan dan sebesar 39 (79,6%) perawat tidak patuh mencuci tangan. Pada analisis bivariat dengan uji Chi-Square menunjukkan bahwa tidak terdapat hubungan sikap perawat dengan kepatuhan perawat mencuci tangan di ruang rawat inap di satu Rumah Sakit Swasta di Jakarta (p value 0,716, CI 95%). Penelitian berikutnya dapat meneliti faktor-faktor lain yang memengaruhi kepatuhan perawat mencuci tangan seperti pengetahuan, motivasi, ketersediaan fasilitas cuci tangan, beban kerja, supervisi dan role model.